Discovery of Traditional Chinese Medicine Derived Compounds as Wild Type and Mutant Plasmodium falciparum Dihydrofolate Reductase Inhibitors: Induced Fit Docking and ADME Studies - Iwaloye, Opeyemi; Elekofehinti, Olusola O.; Kikiowo, Babatomiwa; Fadipe, Toyin Mary; Akinjiyan, Moses Orimoloye; Ariyo, Esther Opeyemi; Aiyeku, Olabisi Olapade; Adewumi, Nicholas Adeyemi (Current Drug Discovery Technologies, 2021)
Background: In a bid to come up with effective compounds as inhibitors for antimalarial treatment, we built a library of 2,000 traditional Chinese medicine(TCM)-derived compounds retrieved from TCM Database@Taiwan. Methods: The active sites of both the wild type and mutant Plasmodium falciparum dihydrofolatereductase (pfDHFR) were explored using computational tools. pfDHFR, one of the prime drug targets in the prevention of malaria infection induced by the female anopheles mosquito has continued to offer resistance to drugs (antifolates) due to mutation in some of the key amino acid residues crucial for its inhibition. Results: We utilized virtual throughput screening and glide XP docking to screen the compounds, and 8 compounds were found to have promising docking scores with both the wild type and mutant pfDHFR. They were further subjected to Induce Fit Docking (IFD) to affirm their inhibitory potency. The ADME properties and biological activity spectrum of the compounds were also considered. The inhibition profile of the compounds revealed that a number of compounds formed intermolecular interactions with ASP54, ILE14, LEU164, SER108/ASN108, ARG122 and ASP58. Most of the compounds can be considered as drug candidates due to their antiprotozoal activities and accordance with the Lipinski’s Rule of Five (ROF). Conclusion: The outcome of the present study should further be investigated to attest the efficacy of these compounds as better drug candidates than the antifolates.
Keywords: antifolates